Micronutrient fertilization enhances ROS scavenging system for alleviation of abiotic stresses in plants - Tavanti, Tauan Rimoldi [UNESP]; Melo, Andressa Aparecida Rodrigues de [UNESP]; Moreira, Luan Dionnes Kaiber [UNESP]; Sanchez, Douglas Enrique Juarez [UNESP]; Silva, Rafael dos Santos [UNESP]; Silva, Ricardo Messias da [UNESP]; Reis, André Rodrigues dos [UNESP] (Elsevier, 2021)
Reactive oxygen species (ROS) such as hydrogen peroxide at low concentrations act as signaling of several abiotic stresses. Overproduction of hydrogen peroxide causes the oxidation of plant cell lipid phosphate layer promoting senescence and cell death. To mitigate the effect of ROS, plants develop antioxidant defense mechanisms (superoxide dismutase, catalase, guaiacol peroxidase), ascorbate-glutathione cycle enzymes (ASA-GSH) (ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase and glutathione reductase), which have the function of removing and transforming ROS into non-toxic substances to maintain cellular homeostasis. Foliar or soil application of fertilizers containing B, Cu, Fe, Mn, Mo, Ni, Se and Zn at low concentrations has the ability to elicit and activate antioxidative enzymes, non-oxidizing metabolism, as well as sugar metabolism to mitigate damage by oxidative stress. Plants treated with micronutrients show higher tolerance to abiotic stress and better nutritional status. In this review, we summarized results indicating micronutrient actions in order to reduce ROS resulting the increase of photosynthetic capacity of plants for greater crop yield. This meta-analysis provides information on the mechanism of action of micronutrients in combating ROS, which can make plants more tolerant to several types of abiotic stress such as extreme temperatures, salinity, heavy metals and excess light.
Keywords: Antioxidant enzymes; Antioxidative metabolism; Oxidative stress; Physiological processes; ROS